Application of continuous biofiltration process for treatment of wastewater contaminated by Bisphenol A (BPA). [Abstract only]. - Ahmari, A.; Nikiema, Josiane; Cabana, H. (2013)
BPA with worldwide production of 4 billion kilograms in 2006 is one of the main emerging pollutants in the world. In 1993 to 2010, around 32.96 tons of BPA was directly discharged to the Canadian environment by industries and in 2008, around11.2 tons specifically have contaminated the water and land. In this project, a series of BPA removal tests was conducted to study the efficiency of a bench scale bio-filter, with a wood chips medium to remove BPA from aqueous solution. Our results showed that the BPA elimination performance was influenced by the hydraulic loading rate and hydrodynamics behavior of the bio-filter. With initial BPA concentration less than 75 ppm, removal efficiency of biofilter was complete and BPA concentration of effluent was not detectable (less than 4.43 ppb).The main two metabolites of BPA biodegradation were 2,2-bis(4-Hydroxyphenyl)-1-propanol and 2,3-bis(4-Hydroxyphenyl)-1,2-propanediol. Based on our knowledge, in this project, for the first time biofilter is applied for removal of emerging contaminants from wastewater and the results represents high efficiency of the system.